Changed nursing scheduling for improved safety culture and working conditions – patients' and nurses' perspectives. (13th January 2016) - Kullberg, Anna; Bergenmar, Mia; Sharp, Lena
Abstract : Aim: To evaluate fixed scheduling compared with self‐scheduling for nursing staff in oncological inpatient care with regard to patient and staff outcomes. Background: Various scheduling models have been tested to attract and retain nursing staff. Little is known about how these schedules affect staff and patients. Fixed scheduling and self‐scheduling have been studied to a small extent, solely from a staff perspective. Method: We implemented fixed scheduling on two of four oncological inpatient wards. Two wards kept self‐scheduling. Through a quasi‐experimental design, baseline and follow‐up measurements were collected among staff and patients. The Safety Attitudes Questionnaire was used among staff, as well as study‐specific questions for patients and staff. Results: Fixed scheduling was associated with less overtime and fewer possibilities to change shifts. Self‐scheduling was associated with more requests from management for short notice shift changes. The type of scheduling did not affect patient‐reported outcomes. Conclusions: Fixed scheduling should be considered in order to lower overtime. Further research is necessary and should explore patient outcomes to a greater extent. Implications for nursing management: Scheduling is a core task for nurse managers. Our study suggests fixed scheduling as a strategy for managers to improve the effective use of resources and safety.